Reliability, validity, and responsiveness of the Japanese version of International Restless Legs Syndrome Study Group rating scale for restless legs syndrome in a clinical trial setting. Issue 6 (5th August 2013) - Inoue, Yuichi; Oka, Yasunori; Kagimura, Tatsuo; Kuroda, Kenji; Hirata, Koichi
Abstract : Aim: This study was conducted to verify the reliability, validity, and responsiveness of the Japanese version of the International Restless Legs Syndrome Study Group Rating Scale for restless legs syndrome (J‐IRLS) as a sub‐study of a clinical trial of pramipexole against restless legs syndrome. Methods: After evaluating the test–retest reliability, concurrent validity and construct validity were analyzed. The responsiveness of J‐IRLS was confirmed by evaluating the correlations between the changes in J‐IRLS total score after treatment, Clinical Global Impression Improvement Scale (CGI‐I), and Patient Global Impression. Results: Test–retest reliability of J‐IRLS was good (intra‐class correlation coefficient, 0.877; 95% confidence interval, 0.802–0.925). The correlation coefficient of J‐IRLS total score and CGI‐S score for the first and second visit was 0.804 and 0.796, respectively (both P < 0.0001). Factor analysis of J‐IRLS itemsalone identified a two‐factor structure. Exploratory analysis on 10 items of J‐IRLS together with the Japanese version of the Pittsburgh Sleep Quality Index revealed that several items on the Japanese version of the Pittsburgh Sleep Quality Index appeared as the third factor. The correlations of CGI‐I and Patient Global Impression with change in J‐IRLS total score after treatment were highly significant. Conclusions: Reliability, validity, and responsiveness of J‐IRLS were considered adequate. The scale is highly applicable both for evaluating the severity of restless legs syndrome and for assessing drug efficacy.